Weed Growth and Lowland Rice Production as Affected by Planting Patterns and Rice Varieties - Rianto, Dwi Fajar; Guntoro, Dwi; Santosa, Edi (Department of Agronomy and Horticulture, IPB University, 2019)
Weeds are one of the most limiting factors in rice cultivation. This study aims to evaluate the eff ects of rice planting patterns on the prevalence of several weed species, Cyperus iria, Echinochloa crusgalli, Fimbristylis miliacea, Leptochloa chinensis, Ludwigia octovalvis, and Spenoclea zeylanica, and to discuss the implications on rice production systems. The research was conducted in IPB Sawah Baru experimental farm in Bogor, West Java, Indonesia, from December 2017 to April 2018. The experiment was arranged in a randomized block design with two factors, rice varieties and rice planting methods. The rice varieties, “IPB 3S” and “Ciherang”, were assigned as the main plot, whereas planting methods, i.e. 25x25 tile, Legowo 2:1 (double rows), Legowo 4:1 (quadruple rows), as sub-plots. The results showed that in the “IPB 3S” plots L. octovalvis shoot dry weight decreased by 33.0%, the root dry weight of L. chinensis roots decreased by 22.6%, and the number of S. zeylanica weed leaves decreased by 28.4% compared to the plots planted with “Ciherang”. With legowo 2:1 planting method the dry weights of L. octovalvis decreased by 21.5%, L. octovalvis by 1.7%, and L. chinensis by 4.4%, and the number of weeds E. crus-galli by 7.0 % compared to Tegel 25x25 method. L. chinensis seemed to be a dominant weed at both vegetative and generative stage of rice development.